Lower Renal Arterial Segmental Variations And Its Urosurgical Importance - DR RAGHAVENDRA V. P,; DR ANJANA TELKAR., (International Journal of Pharma and Bio Sciences, 2012)
Objectives: The advent of more conservative methods in the renal and renal vascular surgeries has necessitated a more precise knowledge of renal vascularization and its importance in partial and total renal transplantation surgeries. Its main objectives :a) To study the Intrarenal arterial segmental patterns especially the lower segmental branch and its variations in 60 human kidneys by dissection, corrosion and radiological method, b) To help the endourologic surgeons to carry out safer surgeries on kidneys, c) To give reliable information to the anatomists for learning and teaching. Methods: Totally 60 adult human kidneys were studied in the present work belonging to both sexes; Out of it 40 were procured from dissection cadavers in the Department of Anatomy, J.J.M. Medical College, Davanagere and 20 fresh kidneys from Mortuary, Chigateri General Hospital, Davanagere. Before removal of the kidneys from the bodies, possibilities of additional apical renal segmental arteries from the common iliac, internal iliac, lumbar, sacral, superior mesenteric, hepatic and inferior suprarenal arteries were looked upon. The segmental arteries of the kidneys were studied by three methods i.e. 10 each by corrosion cast and radiological method.40 by dissections, Results: A total of 60 kidneys were studied, anterior division is classified into 8 types out of it Type VIII showed maximum of 20% and Type II of posterior segment 51.66%. The occurrence of apical, upper, middle and lower remained the normal i.e. of 51.66%, 61.66%, 55% and 51.66% respectively. Conclusion: Much importance is given to the segmental artery which arises in common and divides within the renal parenchyma, as healthy renal tissue is often involved during partial nephrectomy of the affected part.